Kognitive Neurophysiologie des Menschen - Human cognitive neurophysiology Vol. 4 (2011) - (:unkn) unknown; Justus Liebig University Giessen (My University, 2011)
B. Kopp, C. Moschner & K.Wessel: Event-related brain potentials and the functional specialization of human cerebral hemispheres during processing of hierarchical visual stimuli. K. Schneider: Neuroimaging in German court rooms. T. Sauer: Time-frequency analysis, wavelets and why things (can) go wrong. W. Skrandies: Abstracts of the 19th German EEG/EP Mapping Meeting. W. Skrandies: Electrical neuroimaging (Book Review) Announcements - Ankündigungen.
Keywords: ddc:610